Building Information Modelling in Interior Design Processes and its Role in Improving the Quality of Sustainable Interior Spaces (Al-Academy, 2025)
This research aims to validate the integration of building information modelling (BIM) into interior design processes to enhance the quality and sustainability of indoor spaces by improving air quality and lighting quality (BIM) has emerged as a powerful tool in the industries of architecture and construction, revolutionizing the way projects are planned, designed, created and managed however, its application in interior design remains relatively unexplored, especially with regard to sustainable design objectives this study seeks to bridge this gap from the study of how (BIM) can facilitate the creation of sustainable interior spaces while improving the quality. After a thorough review of the literature and case studies, the research will explore the benefits, challenges and potential best practices of applying (BIM) in interior design projects with a focus on sustainability criteria the results will contribute to deeper values of the role of (BIM) in the development of sustainable interior design practices and provide practical insights for professionals, researchers and academics and policy makers in this area